Correlation of the ECG changes (ST segment depression with or without T wave inversion in lateral leads 1, avl. V4-V6) with coronary angiographic findings in ACS patients - Azam, Mohammad Golam; Al-Baker, SME; Rahman, Zillur; Rahman, Md M; Ahmed, Chowdhury M; Benarjee, SK; Ahsan, Syed Ali; Siddique, Abu; Aziz, Mostafizul; Ahmed, Nishat; Hoque, Md Harizul (University Heart Journal, 2014)
No Abstract Available. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19431 University Heart Journal Vol. 9, No. 1, January 2013; 9-12